Correlation between biofilm formation and resistance toward different commonly used antibiotics along with extended spectrum beta lactamase production in uropathogenic Escherichia coli isolated from the patients suspected of urinary tract infections visiting Shree Birendra Hospital, Chhauni, Kathmandu, Nepal - Sanjeev Neupane; Narayan Dutt Pant; Saroj Khatiwada; Raina Chaudhary; Megha Raj Banjara (Antimicrobial Resistance and Infection Control, 2016)
Abstract Background Escherichia coli is the most predominant causative agent of urinary tract infection (UTI). Recently, increase in drug resistance among the uropathogenic bacteria has caused great problem in treatment of UTI. The main objective of this research is to determine the correlation between biofilm formation and resistance toward different commonly used antibiotics along with extended spectrum beta lactamase production in uropathogenic Escherichia coli. Methods The urine samples collected from the patients suspected of urinary tract infections (visiting Shree Birendra Hospital, Chhauni, Kathmandu, Nepal between July to December 2013) were cultured in cystine lactose electrolyte deficient (CLED) agar by using semi quantitative culture technique. Extended spectrum beta lactamase (ESBL) production was detected by combined disc diffusion technique and biofilm formation was detected by Congo red agar method. Chi-square test was applied and p-value < 0.05 was considered statistically significant. Results Out of 1480 urine samples, E. Coli was isolated from 208 (14.1 %) samples. Of total 69 (33.2 %) ESBL producing uropathogenic strains of E. coli, 20 (29 %) were strong biofilm producers, 22 (31.9 %) were moderate biofilm producers, 11 (15.9 %) were weak biofilm producers and 16 (23.2 %) were biofilm non producers. Whereas among 139 ESBL non producing E. coli, 22 (15.8 %) were strong biofilm producers, 20 (14.4 %) were moderate biofilm producers, 13 (9.4 %) were weak biofilm producers and 84 (60.4 %) were biofilm non producers. Among total 108 biofilm producing E. coli, maximum resistance was observed toward cephalexin followed by amoxicillin and highest susceptibility was seen toward amikacin. Conclusion The ability of biofilm formation was found to be significantly higher in ESBL producing strains of E. coli than that in ESBL non producing strains (p < 0.05). There was higher resistance rate to antimicrobial agents among biofilm producing strains of E. coli than that in biofilm non producing strains. According to our antimicrobial susceptibility pattern for E. coli, to start preliminary treatment for UTI in Nepal, we recommend to use amikacin or nitrofurantoin. Further, for the treatment of the UTI, the antibiotics should be selected on the basis of the urine culture and sensitivity report.